The Experiences of Women Entering Methadone Treatment for Opioid Use: an Interpretive Phenomenological Inquiry - (:unkn) unknown (My University, 2013)
The United States is facing a momentous public health problem of prescription and illicit opioid use among women. Traditionally in health literature women have received less attention than men and this is especially true with regard to drug use. In terms of recovery from opioid use, treatment centers that use methadone as a pharmaceutical replacement for illicit opioids have been present in the US for decades, and women have been enrolling in treatment since its inception. However, there is little in the literature about the characteristics of these women, why they choose methadone treatment, and what their experiences are while in treatment. The study explores the experiences of thirteen women entering methadone treatment at a clinic in urban Fort Worth, Texas. Through the narrative descriptions of their history of drug use, reasons for deciding to get help, accounts of why they chose methadone and their experiences during their time in treatment are answered. An Interpretive Phenomenological qualitative research method was employed throughout to gather and understand the stories of women drug users searching for help. This method explores their beliefs about challenges, pitfalls and triumphs of recovery. Results from this study will add to the knowledge base about women and substance use disorders as well as women and change. Findings will help nurses and those in other disciplines to better understand the problem of opioid use among US women and assist women in traversing through the addiction journey.
Keywords: Methadone; Opioid; Substance Use; Treatment; Women